Online Shop Purchase Decision: How Do Social Media Marketing, Electronic Word of Mouth (EWOM), and Lifestyle Affect? - Whan Augustin Ainul Amri; Firdaus Putra; Denny Saputera; Dewiana Novitasari; Jainuri Jainuri (Universitas Muhammadiyah Enrekang, 2023)
The research aims to analyze the effect of social media marketing, electronic word of mouth (EWOM), and lifestyle on purchasing decisions for MSME products sold online. This study uses a type of quantitative research with a sample of 127 student respondents in the city of Tangerang. The hypothesis is tested using structural equation modeling. Data processing uses the SEM method with SmartPLS 3.0 software. The results of the study show that electronic word of mouth (EWOM) and Lifestyle all influence the purchasing decisions of MSME products. Meanwhile, social media marketing has no positive or significant effect on purchasing decision variables. This study contributes to the existing literature by providing empirical evidence about the effect of electronic word of mouth (EWOM) and lifestyle on purchasing decisions. The results of this study also provide evidence that student consumers are more rational and unaffected by social media marketing in making purchasing decisions. The results of this study can also be used by MSME management to attract potential market share in the student segment.